UTILIZING NUSSA AND RARA ANIMATIONS AS CHILDREN'S CHARACTER DEVELOPMENT MEDIA IN UMMI FAUZIAH RANTAUPRAPAT KINDERGARTEN - Anjeli, Rafita Aulia; Prayoga, Yudi; Halim, Abd. (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Technology is one of the most rapidly growing media today. It is important how to utilize technology media as an educational medium. The media most favored by children today are television, laptops, and cell phones/smartphones. However, it cannot be denied that many shows are not entirely good for children to watch. One of the animated films that can provide Islamic moral and educational messages is the Nussa and Rara series. This community service is carried out to make the animated shows Nussa and Rara an educational show in developing children's characters and motivating children to be smart in choosing shows from the internet. This activity takes children's objects at Ummi Fauziah Rantauprapat Kindergarten. The service period is used for 1 day with several series of activities, namely assessing children's behavior through observation and interviews, counseling about character education for children, and watching the Nussa and Rara serials together. The result of this PKM activity is to increase the knowledge and understanding of these school-age children about noble character values ​​and to be motivated to be smarter in choosing good and more educative shows.